Carbon Nanostructures Derived through Hypergolic Reaction of Conductive Polymers with Fuming Nitric Acid at Ambient Conditions - Chalmpes, Nikolaos; Moschovas, Dimitrios; Tantis, Iosif; Bourlinos, Athanasios B; Bakandritsos, Aristides; Fotiadou, Renia; Patila, Michaela; Stamatis, Haralambos; Avgeropoulos, Apostolos; Karakassides, Michael A; Gournis, Dimitrios (Molecules (Basel, Switzerland), 2021)
Hypergolic systems rely on organic fuel and a powerful oxidizer that spontaneously ignites upon contact without any external ignition source. Although their main utilization pertains to rocket fuels and propellants, it is only recently that hypergolics has been established from our group as a new general method for the synthesis of different morphologies of carbon nanostructures depending on the hypergolic pair (organic fuel-oxidizer). In search of new pairs, the hypergolic mixture described here contains polyaniline as the organic source of carbon and fuming nitric acid as strong oxidizer. Specifically, the two reagents react rapidly and spontaneously upon contact at ambient conditions to afford carbon nanosheets. Further liquid-phase exfoliation of the nanosheets in dimethylformamide results in dispersed single layers exhibiting strong Tyndall effect. The method can be extended to other conductive polymers, such as polythiophene and polypyrrole, leading to the formation of different type carbon nanostructures (e.g., photolumincent carbon dots). Apart from being a new synthesis pathway towards carbon nanomaterials and a new type of reaction for conductive polymers, the present hypergolic pairs also provide a novel set of rocket bipropellants based on conductive polymers.
Keywords: carbon nanostructures; conductive polymers; fuming nitric acid; hypergolics; rocket fuels; ambient conditions